STUDY OF TEMPERATURE STABILITY OF PIGMENT OBTAINED FROM clitoria ternatea AND ITS APPLICATION AS NATURAL FOOD COLOUR - Nikita Sawant; Aishwarya Patil; Padmarani Patil; Pratibha Patil; Vidya Patil (The Bioscan, 2025)
Clitoria ternatea is often referred to as the butterfly pea flower. Butterfly peas are easy to grow and flower all year, especially in the summer. Shankapushpi, also known as butterfly pea, is a perennial twining herb found in tropical equatorial areas. The plants are extremely adaptable to changing temperatures and humidity. Plants and microorganisms that produce pigments such as anthocyanins, carotenoids, and chlorophyll are used as natural food colors. Natural coloring agents are gaining popularity, as synthetic colorings have been linked to food intolerance, allergies, irritability, hyperactivity, and sleep disorders in children. Blue pigments are less readily available than red, orange, and yellow pigments. As public awareness of food safety improves, researchers propose utilizing plant-based colorants as a safer alternative to hazardous synthetic dyes. In the present research study, for pigment extraction, Clitoria ternatea flowers and water were mixed in a 1:100 (w/v) ratio and used for each experiment. The extract is subjected to heat treatment & analyzed by UV-visible spectroscopy & calorimetrically for colour stability. The thermal stability of the pigment was studied in pressure-cooked rice (wada kolam). The results showed that the pigment has temperature stability and can serve as a natural food colour for the cooking process.